Desnutrición - LIZBETH AGUILAR NARVÁEZ, IRENE; JANNETH ÁLVAREZ MAYANCELA, LOURDES; MISHEL AYALA NINAZUNTA, ERIKA; LISEÑA CAIZA PULLOTASIG, KAREN; DEL PILAR CHIMA OCHOA, ANA; GABRIELA ESPADERO FAICÁN, ROSA; RAFAEL JARAMILLO, JORGE; Andrade Encalada, Hernán Alonso; Andrade Pino, Kelly Samantha; Angamarca Padilla, Karina Jazmin; arias, diana; Barahona , Nícol Barahona; et al. (Red Editorial Latinoamericana de Investigación Contemporánea, 2024)
Malnutrition has been a persistent problem throughout history, despite advances in agriculture, the food industry and medical technology. Even today, millions of people around the world continue to suffer from hunger and malnutrition. This book aims to explore various issues related to undernutrition, including its causes, such as lack of access to nutritious food, poverty, food insecurity, lack of nutrition education and other social and economic factors that are directly related to undernutrition. In addition, the consequences of malnutrition, such as stunting, muscle weakness, decreased immunity, chronic diseases and infant mortality, will be examined.****In essence, this book on malnutrition serves as a call to action for all members of global society to take responsibility and contribute to the fight against malnutrition. It is not a situation that can be addressed by governments or international organizations alone, but requires the collective commitment of society to ensure that everyone has access to adequate food and can enjoy a healthy and fulfilling life.****This book, which outlines the main advances in programmes, care, tactics and elements related to undernutrition and malnutrition, not only in our nation but also globally, seeks to provide a theoretical and scientific basis for generating knowledge and, potentially, spearheading tactics that will lead to diminishing this dilemma in our environment.****Rosa Gabriela Espadero